Effect of modified atmosphere packaging with varied gas combinations and treatment on the quality of minimally-processed litchi fruits - Putkrong Phanumong (2018)
© 2017, Prince of Songkla University. All rights reserved. This study aimed to select the optimum oxygen (O 2 ) and carbon dioxide (CO 2 ) concentrations for storage of minimally-processed litchi fruit cv. ‘Jugkapat’ packed in a nylon laminated with linear low density polyethylene bag (Nylon/LLDPE). Litchi fruits (fully-red stage) and their arils were sanitized with peroxyacetic acid solutions 100 mg L -1 , 3 min and 50 mg L -1 for 1 min, respectively. Litchi arils were stored under nine combinations of O 2 (2.5, 5.0, and 7.5%) and CO 2 (5.0, 7.5 and 10.0%) with atmospheric nitrogen balance for 18 days at 2±1°C. The optimum concentration of O 2 and CO 2 for storage of minimally-processed litchi fruit was 5.0% and 5.0% due to the lowest levels of juice leakage, ethanol content, microbial growth and maintained firmness the best. The atmosphere of 5.0% O 2 and 5.0% CO 2 maintained the respiratory quotient value closely to 1.0 during storage. The microbial counts are in the microbiological limits for food safety.